Parents’ Knowledge and Children’s Toilet Training Practices: Study in Kindergartens in Jatinangor - Anne Shafira Purnama Claytonia Aziz; Yudith Setiati Ermaya; Nur Melani Sari (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Constipation has serious threats for children, however, this condition can be treated by toilet training. The level of parents’ understanding of defecation affects the success of the training to reduce the symptom of constipation. This study aimed to assess the knowledge of the parents and their children’s practice in toilet training at kindergarten. Methods: This was an analytic study with a cross-sectional method which conducted at kindergartens in Jatinangor, selected by a total random sampling method. A self-made validated questionnaire was distributed to parents asking about knowledge and toilet training. Incomplete answer sheets and parents who did not come to school by the time of the study were excluded. Result: In total, 111 parents returned the questionnaire, and most of the parents (98.19%) had good knowledge regarding toilet training. Moreover, most of the children (96.39%) were also good at practicing the toilet training. There was a strong and significant correlation between parents’ knowledge and the children’s practice of toilet training with coefficient correlation 0.701 and p-value <0.05.Conclusions: Good knowledge of parents help the children practicing toilet training, therefore, education to new parents is necessary.